COD inhibition alleviation and anammox granular sludge stability improvement by biochar addition. (15th April 2022) - Xie, Junxiang; Guo, Menglei; Xie, Jiawei; Chang, Yaofeng; Mabruk, Adams; Zhang, Tian C.; Chen, Chongjun
Abstract: High chemical oxygen demand (COD) in anaerobic ammonium oxidation (anammox) reactors may destroy the structure or inhibite the activity of anammox granular sludge (AnGS). Herein, the effects of adding different biochars on the alleviation of COD inhibition, performance of anammox reactors in phases I (fed with an initial COD = 100 mg L −1 ) and II (= 150 mg L −1 ), as well as their effect on the properties of AnGS granules were investigated. Results showed that nitrogen removal in biochar-added reactors was superior to that in reactors without biochar (the control). AnGS with biochar addition outperformed the control in terms of stability (EPS and particle size distribution) as the initial COD concentration increased. In the reactors amended with litchi biochar and chinar biochar, the respective average TN removal efficiencies were 86.49% and 85.70% in phase Ⅰ as well as 86.54% and 85.51% in phase Ⅱ; the proportion of AnGS particles with a diameter of 1–3 mm reached a respective maximum of 80.97% and 73.74% (much higher than 67.69% in the control); and the AnGS granules had better stability with a little change in the protein (PN) to polysaccharide (PS) (PN/PS) values, the PN/PS values were 4.18 and 4.77 in phase Ⅰ as well as 4.21 and 4.70 in phase Ⅱ. Even at increasing COD concentrations, no significant change in the relative abundance of Planctomycetes was observed in all the biochar-containing reactors (P value over 0.9), and the relative abundance of anammox-related functional genes ( hzs, hdh ) was higher than that in the control. Graphical abstract: Image 1 Highlights: Biochars with larger average pore sizes promoted nitrogen removal performance. Addition biochar enhanced stability of AnGS in the presence of organic carbons. Addition of biochar kept the AnAOB abundance in the presence of organic carbons. Anammox-related genes ( hzs, hdh ) were enriched in all reactors with biochar addition.